Case report: AngioJet thrombectomy with extracorporeal membrane oxygenation support for acute massive pulmonary embolism in a severe multiple trauma patient - Tian, Lun; Zhang, Libin; Zhang, Naiding; Xu, Xin; Xu, Yongshan; Liu, Zhenjie; Huang, Man (Frontiers in Medicine, 2022)
Acute massive pulmonary embolism (PE) is one of the main leading causes of high cardiovascular mortality, and the prognosis strongly varies, depending on the severity of pulmonary arterial obstruction and its impact on the RV function. Alternative therapy approaches comprise systemic thrombolysis, catheter-directed thrombolysis, catheter embolectomy, catheter-assisted fragmentation techniques, and surgical thrombectomy. The succeeding case study explores a 72-year-old man with severe multiple trauma who suffered from a sudden massive pulmonary embolism and presented with an unstable hemodynamic status. Extracorporeal membrane oxygenation (ECMO) has amply proven its efficacy in supplying cardiopulmonary assistance for this patient shocked by a massive PE with contraindication for thrombolysis. Angiojet catheter embolectomy and ECMO were performed, which finally cleared the massive pulmonary embolism away and improved the patient’s hemodynamic status. The use of ECMO was continued during the weaning program, on the fifth day after ECMO decannulation, the patient was extubated and transferred to a local hospital for further recuperation. This case highlights that the AngioJet thrombectomy with the combination use of ECMO may be a potential choice of treatment for unstable PE patients.